Definition of a Prototype of High Temperature Synchronous Reluctance Motor - Elmadah, Hamed; Roger, Daniel; Takorabet, Noureddine (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
This paper discusses the definition of a synchronous reluctance motor with special windings able to work in very hot environments where the ambient temperature rises over 300°C. This motor is designed with inorganic insulated coils able to operate at internal temperatures up to 500°C. With such coils and synchronous reluctance structure, the maximum ambient temperature of using this motor is much over the capabilities of the best magnets. However, this structure has drawback at classical temperatures which it is important to transpose to the extreme temperatures. The paper is dedicated to the construction of a functional prototype which allows the experiments at very high ambient temperatures.